2019
DOI: 10.1155/2019/9301970
|View full text |Cite
|
Sign up to set email alerts
|

Value of Anterior Band of the Inferior Glenohumeral Ligament Area as a Morphological Parameter of Adhesive Capsulitis

Abstract: Objective. Thickened inferior glenohumeral ligament (IGHL) is considered as one of the major morphological parameters of adhesive capsulitis (AC). Previous studies reported that the anterior band of inferior glenohumeral ligament thickness (aIGHLT) is correlated with shoulder capsular contracture, luxatio erecta humeri, and AC. However, the thickness varies from the measured angle. To reduce this measurement error, we devised a new morphological parameter, called the anterior band of inferior glenohumeral liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Zappia et al 12 showed an increase in IGHL signal with high sensitivity and specificity in T2W sequences in patients diagnosed with AC. Bang et al 13 measured the mean IGHL anterior band thickness as 4.52±1.02 mm for the 54 AC patients and 3.47±0.99 mm for the control group. When the information obtained from this study and the information obtained from similar studies are evaluated together, an IGHL value of 4 mm and above can be considered as a favorable criterion for the diagnosis of AC.…”
Section: Discussionmentioning
confidence: 99%
“…Zappia et al 12 showed an increase in IGHL signal with high sensitivity and specificity in T2W sequences in patients diagnosed with AC. Bang et al 13 measured the mean IGHL anterior band thickness as 4.52±1.02 mm for the 54 AC patients and 3.47±0.99 mm for the control group. When the information obtained from this study and the information obtained from similar studies are evaluated together, an IGHL value of 4 mm and above can be considered as a favorable criterion for the diagnosis of AC.…”
Section: Discussionmentioning
confidence: 99%
“…34438 we could say no definitive criteria exist for the diagnosis of adhesive capsulitis to date (8). As a consequence magnetic resonance imaging (MRI) -as the gold standard of shoulder imaging-plays a critical role in diagnosis of adhesive capsulitis, in the early stages (9). Studies on histological aspects of adhesive capsulitis suggest the predominance of abnormalities in the anterior joint capsule, which include accumulation of myofibroblasts and collagenous matrix, focal fibrosis, inflammatory cytokines, regenerative neural fibers and increased vascularity in this region, which is interestingly absent in the inferior portion (2).…”
Section: Key Pointmentioning
confidence: 99%
“…Plain-film X-rays of the shoulder should be done, but the findings are usually normal and other imaging studies are occasionally necessary for the differential diagnosis. Characteristic signs on ultrasonography and magnetic resonance imaging include thickening of the inferior glenohumeral ligament, coracohumeral ligaments, and axillary pouch as well as infiltration of the rotator interval, this thickening and contraction of the shoulder joint capsule and surrounding synovium is better defined by MRI [8][9][10][11][12][13] . Adhesive capsulitis is defined as a self-limiting condition, with different stages (painful, mobidity limitation and clinical recovery) and symptoms length between months to years.…”
Section: Introductionmentioning
confidence: 99%